Efficacy of casein phosphopeptide varnish reducing dental hypersensitivity: a randomized clinical trial - Bapn, Rakhi A; Shetty, Neema; Mathur, Aditi; Bali, Ashish; Taki, Mumtak; Devani, Vivek R (Iberoamerican journal of medicine, 2021)
Abstract Introduction: Dentin hypersensitivity (DH) is the most common concern faced by most dentists in their day-to-day clinical practice. It is characterized by short-term, acute pain of variable intensity, which occurs in response to thermal, tactile, osmotic or chemical stimuli that cannot be attributed to any other type of defect or dental decay. Casein phosphopeptide varnish is a newer material used to treat dentinal hypersensitivity as it reduces demineralization and promotes remineralization. The aim of this study is to evaluate the efficacy of casein phosphopeptide based varnish (MI Varnish®) vs sodium fluoride-based varnish (Fluoritop SR® varnish) in treating dentinal hypersensitivity. Materials and methods: 40 subjects with a chief complaint of DH were divided into two equal groups, Group A (MI varnish®) and Group B (Fluoritop SR® varnish). Scaling and root planing was done and sensitivity was assessed using Visual analog scale (VAS) at baseline. On the 14th day, sensitivity was reassessed using VAS. The data obtained were subjected to statistical analysis using students‘t’ test. Results: On intragroup comparison, VAS scale showed a statistically significant difference for both the groups. On intergroup comparison, no statistical difference was found between both groups (p = 0.139). Conclusions: From the above results, it can be concluded that MI varnish® and Fluoritop SR® varnish are equally efficacious in reducing dentinal hypersensitivity.